2007
DOI: 10.1515/cclm.2007.300
|View full text |Cite
|
Sign up to set email alerts
|

Developmental changes in the L-arginine/nitric oxide pathway from infancy to adulthood: plasma asymmetric dimethylarginine levels decrease with age

Abstract: Background: The L-arginine/nitric oxide (NO) pathway has multiple physiological functions including vasodilation, inhibition of platelet aggregation and neurotransmission. Asymmetric dimethylarginine (ADMA), an endogenous inhibitor of all known NO synthase isoforms, has adverse effects on renal and cardiovascular function in adults. It is unknown whether ADMA might also exert similar effects in younger individuals including infants. Also, reference data for important members of the L-arginine/NO family, notabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
41
1
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 38 publications
10
41
1
1
Order By: Relevance
“…Interestingly, ADMA synthesis is higher in children compared to adults, yet without signs of cardiovascular diseases. In healthy humans, ADMA synthesis decreases steadily from infancy to adulthood (Lücke et al 2007). We were interested to know whether the L-Arg/NO pathway is altered in children with DMD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, ADMA synthesis is higher in children compared to adults, yet without signs of cardiovascular diseases. In healthy humans, ADMA synthesis decreases steadily from infancy to adulthood (Lücke et al 2007). We were interested to know whether the L-Arg/NO pathway is altered in children with DMD.…”
Section: Discussionmentioning
confidence: 99%
“…DMD patients affected more severely are usually older than less affected DMD patients. This circumstance and the age-dependent decrease of circulating ADMA in healthy children (Lücke et al 2007) may explain in part the lack of a correlation between plasma ADMA concentration and stage of disease in the DMD patients.…”
Section: The L-arg/no Pathway In Relation To the Dmd Stage Of Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…High ADMA levels have been found in adults with type 1 diabetes mellitus (T1DM) compared to healthy controls (Altinova et al 2007;Marcovecchio et al 2011). In previous studies, we reported on developmental changes in the Arg/NO pathway from infancy to adulthood, showing a decrease in plasma ADMA levels with age (Lücke et al 2007), as well as in metabolic diseases (Lücke et al 2006(Lücke et al , 2008ChobanyanJürgens et al 2012a;Kanzelmeyer et al 2012) (Fig. 1).…”
Section: Introductionmentioning
confidence: 88%
“…The cardiovascular risk assigned to ADMA in adults is likely to arise from other not yet recognized actions of ADMA. Children have much higher circulating ADMA concentrations than adults (29), but there is no evidence that children have a risk for cardiovascular disease. In humans, the activity of eNOS, nNOS, and iNOS is steadily inhibited by ADMA and other endogenous inhibitors, and L-arginine administration can reduce the extent of this baseline inhibition to almost the same degree, albeit by different mechanisms.…”
Section: Resultsmentioning
confidence: 99%